Analysis of Indonesia Coffee Seed Export Competitiveness - Jan Hotman; Albert Gamot Malau (Dinasti International Journal of Management Science, 2022)
Indonesia is rich in agricultural production sources, one of which is coffee commodity which is exported to various countries. So the purpose of this study is to find out the competitiveness of Indonesian coffee in the international market. The analysis tools used are Revealed Comparative Advantage (RCA) and Export Product Dynamic (EPD) to see the competitiveness of exports of coffee bean commodities (HS 1801) to destination countries. The results of the analysis by the RCA method show that Indonesian coffee beans have an average value of RCA greater than one in the export destination country. Based on the results of the EPD analysis showed that Indonesia's coffee beans export destination countries occupy the position of rising star only Japan, Germany, Belgium and India which are not included. Japan and Belgium are in the falling star position, India has lost opportunity and in the meantime Germany is in a retreat position.